Dopamine overdose hypothesis: Evidence and clinical implications. Issue 14 (9th October 2013) - Vaillancourt, David E.; Schonfeld, Daniel; Kwak, Youngbin; Bohnen, Nicolaas I.; Seidler, Rachael
ABSTRACT About a half a century has passed since dopamine was identified as a neurotransmitter, and it has been several decades since it was established that people with Parkinson's disease receive motor symptom relief from oral levodopa. Despite the evidence that levodopa can reduce motor symptoms, there has been a developing body of literature that dopaminergic therapy can improve cognitive functions in some patients but make them worse in others. Over the past two decades, several laboratories have shown that dopaminergic medications can impair the action of intact neural structures and impair the behaviors associated with these structures. In this review, we consider the evidence that has accumulated in the areas of reversal learning, motor sequence learning, and other cognitive tasks. The purported inverted‐U shaped relationship between dopamine levels and performance is complex and includes many contributory factors. The regional striatal topography of nigrostriatal denervation is a critical factor, as supported by multimodal neuroimaging studies. A patient's individual genotype will determine the relative baseline position on this inverted‐U curve. Dopaminergic pharmacotherapy and individual gene polymorphisms can affect the mesolimbic and prefrontal cortical dopaminergic functions in a comparable, inverted‐U dose‐response relationship. Depending on these factors, a patient can respond positively or negatively to levodopa when performing reversal learning and motor sequence learning tasks. These tasks may continue to be relevant as our society moves to increased technological demands of a digital world that requires newly learned motor sequences and adaptive behaviors to manage daily life activities. © 2013 International Parkinson and Movement Disorder Society